Male pseudohermaphroditism resulting from a novel mutation in the human steroid 5 alpha-reductase type 2 gene (SRD5A2). Issue 1 (February 1997) - Anwar, R; Gilbey, S G; New, J P; Markham, A F
Abstract : The enzyme steroid 5 alpha-reductase, via NADPH, catalyses the conversion of testosterone to dihydrotestosterone, which is required for the embryonic differentiation of the external male genitalia and the prostate. An impairment of this reaction causes a form of male pseudohermaphroditism in which genetic males differentiate predominantly as phenotypic females. Molecular analysis of the 5 alpha-reductase type 2 gene in a patient with confirmed biochemical 5 alpha-reductase deficiency has resulted in the identification of a novel mutation, GAA to AAA, at codon 200. This mutation produces an amino acid change from glutamic acid to lysine, and may affect the ability of the enzyme to bind its co-factor.